2008
DOI: 10.1007/bf03195624
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine,MTHFR gene polymorphisms, and cardio-cerebrovascular risk

Abstract: Vascular diseases are commonly associated with traditional risk factors, but in the last decade scientific evidence has suggested that elevated plasma levels of homocysteine are associated with an increased risk of atherosclerosis and cardiovascular ischaemic events. Cardio- and cerebrovascular diseases are multifactorial, as their aetiopathogenesis is determined by genetic and environmental factors and by gene-gene and gene-environment interactions. Experimental studies have shown that many possible mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
81
0
22

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(103 citation statements)
references
References 152 publications
0
81
0
22
Order By: Relevance
“…The TT genotype of C677T polymorphism in MTHFR gene was associated with elevated plasma homocysteine level, increased risk of arterial stiffness (Trabetti 2008). Women with elevated total homocysteine concentrations showed a significant association with defective chorionic villous vascularization (Nelen et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The TT genotype of C677T polymorphism in MTHFR gene was associated with elevated plasma homocysteine level, increased risk of arterial stiffness (Trabetti 2008). Women with elevated total homocysteine concentrations showed a significant association with defective chorionic villous vascularization (Nelen et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…1 Flow chart shows study selection procedure. Twenty-five case-control studies were included in present meta-analysis was associated with elevated plasma homocysteine level, increased risk of arterial stiffness [58] and women with elevated total homocysteine concentrations showed a significant association with defective chorionic villous vascularization [59][60][61]. In embryonic development during pregnancy, the embryo survives and grows by stimulating its own blood supply through angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the clinical evolution of arterial or venous thrombotic events in patients with MTHFR gene mutation and increased homocysteine levels improves under supplementation with folic acid, as seen also in this case report. 10 Gene disorders that affect clotting factor V, prothrombin, and homocysteine, increase the risk of developing acute coronary syndromes or stroke, especially at a young age. 11 Nevertheless, the screening protocol applies to a relatively low number of subjects, since the number of …”
Section: Discussionmentioning
confidence: 99%